China’s achievements in poverty reduction - Pęciak, Renata (Chińskie osiągnięcia w ograniczaniu ubóstwa, 2020)
In 1978 in China, nearly 250 million citizens lived under the official poverty line, and the poverty rate was 30.7%, which by 2018 fell to 0.6%. The purpose of the paper is to review the history of China’s poverty reduction strategy. The statistical data, covering the period from the beginning of the economic reforms to 2018/2019, show the process that took place in reducing poverty in China. Although the main goal of the reforms undertaken by Deng Xiaoping was to improve living conditions in China, no targeted policy was applied in the initial period. From the mid-1980s onwards the systematic and targeted actions but also successive modification and adjustment of the implemented programs allowed to continue the fight against poverty, especially in rural areas. Despite the obvious success, China still faces major challenges. It is necessary to lead a more precise orientation of poverty relief policies, but also through the coordination of the antipoverty strategy and confronting it with practices
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 12, s. 71-86